'I wasn't worried because I wasn't being judged': The development of pre-service teacher professional capital, pedagogical instinct and discretionary judgement during an overseas teaching placement. (April 2022) - Witt, Marcus; Lewis, Fay; Knight, Ben
Abstract: Assertions that experiences of teaching abroad encourage professional growth for pre-service teachers (PSTs) are discussed, with reference to reflections from 20 PSTs from a British university after a volunteer teaching placement in South Africa (SA). PSTs compare their overseas and domestic placement experiences. Data reveals that capacity for decisional judgement, willingness to follow professional instincts and take risks are influenced by perceived levels of professional scrutiny. Teacher expertise is discussed through the conceptual lens of professional capital. We conclude that decisional judgement and the skills to think on one's feet, are more likely to flourish under non-judgmental conditions.